2014
DOI: 10.4134/jkms.2014.51.4.679
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Richardson Extrapolation on Some Numerical Methods for a Singularly Perturbed Turning Point Problem Whose Solution Has Boundary Layers

Abstract: Abstract. Investigation of the numerical solution of singularly perturbed turning point problems dates back to late 1970s. However, due to the presence of layers, not many high order schemes could be developed to solve such problems. On the other hand, one could think of applying the convergence acceleration technique to improve the performance of existing numerical methods. However, that itself posed some challenges. To this end, we design and analyze a novel fitted operator finite difference method (FOFDM) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Kadalbajoo et al [13] also suggested B-spline collocation with artificial viscosity on uniform mesh for the same class of SPTPP (1.1)-(1.5). In [18], Munyakazi and Patidar conclude that convergence acceleration Richardson extrapolation technique on existing numerical schemes for the above class of turning point problem does not improve the rate of convergence. However, Becher and Roos [4] show that Richardson extrapolation on upwind scheme with piecewise-uniform Shishkin mesh works fine and improves the accuracy to O(N −2 ln 2 N ) under the assumption ε ≤ CN −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Kadalbajoo et al [13] also suggested B-spline collocation with artificial viscosity on uniform mesh for the same class of SPTPP (1.1)-(1.5). In [18], Munyakazi and Patidar conclude that convergence acceleration Richardson extrapolation technique on existing numerical schemes for the above class of turning point problem does not improve the rate of convergence. However, Becher and Roos [4] show that Richardson extrapolation on upwind scheme with piecewise-uniform Shishkin mesh works fine and improves the accuracy to O(N −2 ln 2 N ) under the assumption ε ≤ CN −1 .…”
Section: Introductionmentioning
confidence: 99%
“…A reproducing kernel method was employed for solving Equation (1.1) by Geng and Qian [13]. Munyakazi and Patidar developed a fitted-mesh finite difference method with Richardson extrapolation in [28]. For solving Equation (1.1), a fitted-operator scheme was constructed by Phaneendra et al in [34] using nonsymmetric finite differences for the first-order derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In Kadalbajoo et al a B‐spline collocation method is designed. Readers who need more information related to nonturning points time dependent singularly perturbed parabolic problems may refer to , and those who are interested in time dependent singularly perturbed parabolic problems when the turning points lead to boundary and/or interior layer(s) are referred to .…”
Section: Introductionmentioning
confidence: 99%
“…We show that the method converges uniformly of order one in both space and time variables. We also use Richardson extrapolation , as the acceleration technique to improve the accuracy and the order of convergence of the FOFDM designed up to order two in space only.…”
Section: Introductionmentioning
confidence: 99%